2018
DOI: 10.1155/2018/5847081
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Weak Signal Detection Method of Electromagnetic LWD Based on a Duffing Oscillator

Abstract: The logging while drilling (LWD) electromagnetic weak signal detection model of a Duffing oscillator based on a one-dimensional nonlinear oscillator is established. The influences of noise on Duffing oscillator dynamic behavior of periodic driving force are discussed and evaluate the oscillator weak signal detection mechanism based on a phase change trajectory diagram. The improved Duffing oscillator is designed and applied to detect the electromagnetic logging signal resistivity at the drill bit using the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Despite the fact that noise can be very large, it can only influence the local trajectory on the phase plane diagram, not create phase transitions. When a signal s(t) has the same frequency as the reference signal, it is buried in noise [5]. As a result, if d exceeds dcr, a phase transition will occur, and the large periodic motion will draw it out of the background noise.…”
Section: Some Weak Signal Detection Techniques 21 Chaotic Detection S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that noise can be very large, it can only influence the local trajectory on the phase plane diagram, not create phase transitions. When a signal s(t) has the same frequency as the reference signal, it is buried in noise [5]. As a result, if d exceeds dcr, a phase transition will occur, and the large periodic motion will draw it out of the background noise.…”
Section: Some Weak Signal Detection Techniques 21 Chaotic Detection S...mentioning
confidence: 99%
“…A stochastic resonance is a nonlinear event in a modulated bistable system or multistable system generated by periodic signals with additional noise. It is illustrated by the second-order nonlinear differential equation [23], expressed as (5).…”
Section: Stochastic Resonance (Sr) 231 Basic Model Of Bistable Srmentioning
confidence: 99%
“…Essentially, chaotic systems present a high sensitivity to a minute variations of their initial conditions or a tiny perturbations, such that even a very slight disturbance can lead to that the motion track deviates completely from the system's original trajectory after a certain period of evolution. so chaotic system is widely employed in digital watermarking [1][2][3], pseudo noise code generation [4][5][6], image encryption [7][8][9], weak signal detection [10][11][12] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [ 30 ] designed an improved Duffing chaotic system and applied it to the resistivity detection of a near-bit electromagnetic logging signal. The test results showed that the smaller the amplitude of the tested signal, the more sensitive and noise resistant the system is to the signal, and the lower the SNR of the detectable signal.…”
Section: Introductionmentioning
confidence: 99%